2000
DOI: 10.1258/0022215001905625
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoma of the mastoid bone: solitary and systemic

Abstract: Plasma cell tumours of the mastoid are rare malignancies of haematological origin. Two patients are described with a plasma cell tumour in the mastoid bone. In one patient it concerned a solitary plasmacytoma of the bone and in the other a focus in the mastoid of a recently diagnosed multiple myeloma. Symptoms in these patients were non-specific. Computed tomography (CT) and magnetic resonance image (MRI) scanning showed a non-specific space-occupying lesion in the mastoid. The diagnosis was made on immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…As noted above, the possibility of a lesion presenting in the absence of a previous MM diagnosis exists, and it is also noteworthy that some cases of SPB are not clearly associated with systemic disease even with years of follow-up (3,20). The findings of the present study suggest that MM is ultimately associated with SPB of the temporal bone in approximately half of cases.…”
Section: Discussionsupporting
confidence: 61%
“…As noted above, the possibility of a lesion presenting in the absence of a previous MM diagnosis exists, and it is also noteworthy that some cases of SPB are not clearly associated with systemic disease even with years of follow-up (3,20). The findings of the present study suggest that MM is ultimately associated with SPB of the temporal bone in approximately half of cases.…”
Section: Discussionsupporting
confidence: 61%
“…Plasma cell neoplasm is radiosensitive; therefore, local debulking followed by radiotherapy had a good result on it. Once disease becomes multiple myeloma, then prognosis is not as good as plasmacytoma; chemotherapy should be added [13,14] . The potential for malignant systemic progression is higher for solitary plasmocytomas of bone than for extramedullary plasmocytomas [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of CNS plasmacytomas changes according to the extent of the disease, in solitary tumors, local surgical debulking followed by radiotherapy have shown good outcomes but once the disease becomes systemic, chemotherapy is the main treatment [23,24,25]. It has been reported that extramedullary localizations of myeloma originating from the cranial bone usually respond well to new drugs (e.g., thalidomide, bortezomid and lenalidome) compared tointraparenchyma plasmacytomas [26].…”
Section: Discussionmentioning
confidence: 99%